The symbolic meaning of Javanese Keris’ Patra ornament using ethnolinguistic approach - Izzati, Ana Nugrahaini; Mulyana, Mulyana (citeus, 2020)
This study aimed to describe and to know the terms and symbolic meanings of Javanese keris’ patra ornaments. The meaning is not only lexical but also cultural; meaning which is associated with the civilization prevailing in that society. This research is a descriptive study using ethnolinguistic approach. Ethnolinguistic approach is used to uncover the meaning of the term patra deder which is related to local culture. The results of this study indicated that the patra ornament of Javanese keris has certain terms in each part. The meaning contained in the patra deder of Javanese keris is related to human life. It means that religious support, behaving politely and not arrogant, respecting each other, being responsible, obeying the prevailing norms and having positive thought are substantial in human life.